Faktor-Faktor yang Mempengaruhi Kualitas Pengungkapan Laporan Keuangan dalam Website Pemerintah Daerah: Studi Empiris pada Kabupaten dan Kota di Indonesia - Yuni Yuni; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to determine the effect of regional expenditure, administrative age, regional wealth, per capita income, audit opinion, and local revenue on the quality of disclosure of financial statements on local government websites. This research is a causative research. The population and sample of the study are the financial statements of district and city governments in Indonesia in 2019. The sampling technique used is purposive sampling. The type of data is secondary data. The collection technique is carried out by the documentation method, namely collecting local government financial report data and reviewing each local government website. The data analysis method used is multiple regression analysis with regional expenditure, administrative age, regional wealth, per capita income, audit opinion, and local revenue as the dependent variable and the quality of disclosure of financial statements on local government websites as independent variables. The results showed that audit opinion and local revenue had an effect on the quality of disclosure of financial statements on local government websites, while regional spending, administrative age, regional wealth, per capita income did not affect the quality of disclosure of financial statements on local government websites.